Problem solving and data analysis using Minitab : a clear and easy guide to Six Sigma methodology - Khan, Rehman M. (2013)
"Problem Solving and Data Analysis using Minitab presents example based learning to aid readers in understanding how to use MINITAB 16 for statistical analysis and problem solving"--
Includes index.
Keywords: Minitab; Mathematical statistics -- Data processing; Problem solving -- Statistical methods; Six sigma (Quality control standard); MATHEMATICS / Probability & Statistics / General